Development of phosphate rock integrated with iron amendment for simultaneous immobilization of Zn and Cr(VI) in an electroplating contaminated soil. (September 2017) - Zhao, Ling; Ding, Zhenliang; Sima, Jingke; Xu, Xiaoyun; Cao, Xinde
Abstract: This study aims to develop an amendment for simultaneous immobilization of Zn and Cr(VI) in an abandoned electroplating contaminated soil. Nature phosphate rock was first activated with oxalic acid (O-PR) and then combined with FeSO4 or zero-valent iron (ZVI) for immobilization of Zn and Cr(VI) from aqueous solutions. Finally, the optimized approach showing the highest immobilization ability in solution was applied in an electroplating contaminated soil. The O-PR combined with FeSO4 was more effective in simultaneously removing Zn and Cr(VI) than the O-PR integrated with ZVI within the tested solution pH range of 5.5–8.5. Both O-PR with FeSO4 and with ZVI removed over 95% of Zn from the solution; however, only 42–46% of Cr(VI) was immobilized by O-PR with ZVI, while O-PR with FeSO4 almost precipitated all Cr(VI). Moreover, there were 75–95% Zn and 95–100% Cr(VI) remaining in the exhausted O-PR with FeSO4 solid after toxicity characteristic leaching test (TCLP) while the exhausted O-PR with ZVI solid only retained 44–83% Zn and 32–72% Cr(VI). Zinc was immobilized mainly via formation of insoluble Fe-Zn phosphate co-precipitates, while iron-induced reduction of Cr(VI) into stable Cr(OH)3 or Crx Fe(1-x) (OH)3 was responsible for Cr(VI) immobilization. Application of the O-PR integrated with FeSO4 in the electroplating contaminated soil rapidly reduced the TCLP extractable Zn and Cr(VI) to below the standard limits, with decrease by 50% and 94%, respectively. This study revealed that combination of oxalic acid activated phosphate rock with FeSO4 could be an effective amendment for remediation of Zn and Cr(VI) contaminated soil. Graphical abstract: Highlights: O-PR + FeSO4 was more effective than O-PR + ZVI in immobilizing Zn and Cr(VI) simultaneously. Cr(VI) was reduced by Fe(II) into Cr(III) and form insoluble Fe-involved precipitates. Zn immobilization was due to formation of insoluble Fe-Zn-phosphate. In electroplating soil, O-PR + FeSO4 immobilized about 50% and 94% of Zn and Cr(VI).